Seven myths about education - Christodoulou, Daisy, ....- (London : Routledge, 2014)
In this controversial new book, Daisy Christodoulou offers a thought-provoking critique of educational orthodoxy. Drawing on her recent experience of teaching in challenging schools, she shows through a wide range of examples and case studies just how much classroom practice contradicts basic scientific principles. She examines seven widely-held beliefs which are holding back pupils and teachers: - Facts prevent understanding - Teacher-led instruction is passive - The 21st century fundamentally changes everything - You can always just look it up -We should teach transferable skills - Projects and activities are the best way to learn - Teaching knowledge is indoctrination. In each accessible and engaging chapter, Christodoulou sets out the theory of each myth, considers its practical implications and shows the worrying prevalence of such practice. Then, she explains exactly why it is a myth, with reference to the principles of modern cognitive science. She builds a powerful case explaining how governments and educational organisations around the world have let down teachers and pupils by promoting and even mandating evidence-less theory and bad practice. This blisteringly incisive and urgent text is essential reading for all teachers, teacher training students, policy makers, head teachers, researchers and academics around the world.
Includes bibliographical references and index.
Keywords: Education -- Research -- Case studies; Education -- Philosophy -- Case studies